Nonreciprocal vortex isolator via topology-selective stimulated Brillouin scattering - Zeng, Xinglin; Russell, Philip St. J.; Wolff, Christian; Frosz, Michael H.; Wong, Gordon Kwan Leung; Stiller, Birgit (Science Advances, 2022)
Optical nonreciprocity, which breaks the symmetry between forward and backward propagating optical waves, has become vital in photonic systems and enables many key applications. So far, all the existing nonreciprocal systems are implemented for linearly or randomly polarized fundamental modes. Optical vortex modes, with wavefronts that spiral around the central axis of propagation, have been extensively studied over the past decades and offer an additional degree of freedom useful in many applications. Here, we report a light-driven nonreciprocal isolation system for optical vortex modes based on topology-selective stimulated Brillouin scattering (SBS) in chiral photonic crystal fiber. The device can be reconfigured as an amplifier or an isolator by adjusting the frequency of the control signal. The experimental results show vortex isolation of 22 decibels (dB), which is at the state of the art in fundamental mode isolators using SBS. This device may find applications in optical communications, fiber lasers, quantum information processing, and optical tweezers.
CRIS-Team Scopus Importer:2022-11-04